Laser light and Environment: Exploring the Applications and Impact of Laser Technology (Journal of Advances and Scholarly Researches in Allied Education, 2015)
A laser is a coherent and focused beam of photons. The acronym laser remains for "light amplification by stimulated emission of radiation." Lasers work because of resonant impacts. This paper clarify the laser and its day by day utilize.